2022
DOI: 10.3389/fpsyg.2022.999045
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of information and communications technology on green growth and environmental performance, socio-economic and environmental cost of technology generation: A pathway toward environment sustainability

Abstract: Human capital and ICT have a significant role in determining human development. The impacts of ICT and human capital on green growth and environmental sustainability should be explored for sustainable economic development. This research contributes to the literature on the role of ICTs and human capital in the determination of green growth and environmental performance. Based on time-series data 1990–2019, the study intends to investigate the impact of ICTs and human capital on environmental and green growth p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…The study findings have revealed that the ICT investment is crucial for facilitating and encouraging the adoption of renewable energy, which is supported by the existing literature [ 44 , 45 , 48 , 50 , 54 , 116 , 117 ]. The study of Wang, Qamruzzaman [ 8 ], Qamruzzaman and Kler [ 18 ], Su, Wang [ 47 ], Santarius, Bieser [ 49 ] revealed that ICT is crucial in seamlessly incorporating renewable energy sources into the current energy infrastructure; additionally, it empowers consumers by providing them with the necessary information to make well-informed and environmentally conscious energy decisions [ 45 ].…”
Section: Discussion Of the Study Findingssupporting
confidence: 80%
See 1 more Smart Citation
“…The study findings have revealed that the ICT investment is crucial for facilitating and encouraging the adoption of renewable energy, which is supported by the existing literature [ 44 , 45 , 48 , 50 , 54 , 116 , 117 ]. The study of Wang, Qamruzzaman [ 8 ], Qamruzzaman and Kler [ 18 ], Su, Wang [ 47 ], Santarius, Bieser [ 49 ] revealed that ICT is crucial in seamlessly incorporating renewable energy sources into the current energy infrastructure; additionally, it empowers consumers by providing them with the necessary information to make well-informed and environmentally conscious energy decisions [ 45 ].…”
Section: Discussion Of the Study Findingssupporting
confidence: 80%
“…The study findings have revealed that the ICT investment is crucial for facilitating and encouraging the adoption of renewable energy, which is supported by the existing literature [44,45,48,50,54,116,117]. The study of Wang, Qamruzzaman [8], Qamruzzaman and Kler [18], Su,…”
Section: Discussion Of the Study Findingssupporting
confidence: 69%
“…For example, Xiao discuss the non-linear impact of digitalization level on the carbon emission performance of enterprises (Xiao and Wang 2023). Digital technology can revolutionize traditional industries, leading to increased intelligence and sustainability (Chen et al 2022). This transformation can bring higher value and lower energy consumption and carbon emissions.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…As a result, many scholars have conducted research on the cultivation of environmental talents, and some scholars have studied the role of human capital in green growth and environmental performance, which has shown that increased investment in human capital can promote green economic growth and realize environmental protection [47]. Yang et al [48] empirically analyzed the impact of natural disasters on agricultural production decisions using the probit model.…”
Section: Introductionmentioning
confidence: 99%